Parliamentary oversight of the executives : tools and procedure in Europe - Griglio, Elena, 1978- (Oxford, UK ; Hart Publishing, 2020)
"Oversight of executives has always been a key function of parliaments and one which is central to developing the relationship between the executive and legislative branches of government. However, in reality governments are taking a more pronounced role in controlling legislation, diluting the influence of parliament. This book plots this trend in parliaments across Europe, to illustrate points of convergence and divergence. In so doing, it suggest tools and methods that parliaments can develop to bolster their crucial oversight role"--
Introduction : oversight of the executives : a European approach -- Oversight as a relational function linking parliaments to executives -- Instances of parliamentary oversight in dialogue with other parliamentary functions -- Classifying oversight tools according to parliamentary practice -- Parliamentary oversight in bicameral systems : what role for upper houses? -- Parliaments in international affairs : fostering democracy through the oversight of government action -- Parliamentary oversight in the EU constitutional dimension : the polycentric paradigm -- Parliamentary oversight of budget : a trade-off with budgetary decision-making? -- Conclusions : from law-making to oversight? : a concrete perspective for European parliamentarism.
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Legislative oversight -- Europe; International law; Electronic books